Human Papillomavirus Type 16 Induced Squamous Cell Carcinoma (In situ) of the Toes - Alexander Kreuter; Georgios Mitrakos; Bijan Koushk-Jalali; Thomas Kuntz; Frank Oellig; Christian Tigges; Steffi Silling; Ulrike Wieland (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)